Cryonics, euthanasia, and the doctrine of double effect - Gabriel Andrade; Maria Campo Redondo (Philosophy, Ethics, and Humanities in Medicine, 2023)
Abstract In 1989, Thomas Donaldson requested the California courts to allow physicians to hasten his death. Donaldson had been diagnosed with brain cancer, and he desired to die in order to cryonically preserve his brain, so as to stop its further deterioration. This case elicits an important question: is this a case of euthanasia? In this article, we examine the traditional criteria of death, and contrast it with the information-theoretic criterion. If this criterion is accepted, we posit that Donaldson’s case would have been cryocide, but not euthanasia. We then examine if cryocide is an ethically feasible alternative to euthanasia. To do so, we rely on the ethical doctrine of double effect.